THE LINGUISTIC PHILOSOPHY OF NOAM CHOMSKY - Buniyatova, Isabella (Studia Philologica, 2021)
The paper offers a preliminary overview of the Chomskian revolution in linguistics, with special emphasis laid on his anthropological stance. The pivotal ideas of language faculty as a cognitive capacity of mind, language creativity that follows from the fundamentals of philosophical rationalism, generative procedure, as well as aims of to-date linguistic theory are highlighted.